1997
DOI: 10.1046/j.1469-8137.1997.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of sugars by intraradical hyphae of arbuscular mycorrhizal fungi revealed by radiorespirometry

Abstract: SUMMARYEvolution of ^*CO2 from onion roots and the intraradical hyphae of Gigaspora margarita Becker & Hall was examined by radiorespirometry after addition of ^*C-labelled glucose or sucrose to mycorrhizal or nonmycorrhizal roots. In mycorrhizas, the respiration rate from glucose was about twice that from sucrose. The respiration rate from glucose in the mycorrhizas was much higher than that in the non-mycorrhizal roots, but no differences between mycorrhizal and non-mycorrhizal roots were found in the respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
107
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(112 citation statements)
references
References 22 publications
2
107
1
Order By: Relevance
“…Nevertheless, this assumption would be in strong contrast to several other studies that examine the induction of Suc-cleaving enzymes in mycorrhizal roots (e.g. Dehne, 1986;Snellgrove et al, 1987;Wright et al, 1998;Hohnjec et al, 2003;Schaarschmidt et al, 2006) and also to the fact that isolated intraradical hyphae showed a high preference for the uptake of Glc compared to Suc and Fru (Solaiman and Saito, 1997). To vitiate this assumption, we have shown the importance of acid invertases in the AM association by repressing their enzymatic activity.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Nevertheless, this assumption would be in strong contrast to several other studies that examine the induction of Suc-cleaving enzymes in mycorrhizal roots (e.g. Dehne, 1986;Snellgrove et al, 1987;Wright et al, 1998;Hohnjec et al, 2003;Schaarschmidt et al, 2006) and also to the fact that isolated intraradical hyphae showed a high preference for the uptake of Glc compared to Suc and Fru (Solaiman and Saito, 1997). To vitiate this assumption, we have shown the importance of acid invertases in the AM association by repressing their enzymatic activity.…”
Section: Discussioncontrasting
confidence: 68%
“…Moreover, the incorporation of isotopically labeled Glc into trehalose and glycogen was found to depend on the presence of arbuscules (Pfeffer and Shachar-Hill, 1996) and the latter could be correlated with spore formation (Douds, 1994). However, isolated intraradical hyphae showed efficient uptake of Glc, suggesting the putative involvement of hyphae in carbon uptake as well (Solaiman and Saito, 1997).In addition to labeling experiments, the exchange of carbon in the form of hexoses is further supported by transcript accumulation of a mycorrhiza-induced hexose transporter from M. truncatula in colonized root areas (Harrison, 1996). This suggests an active transport of hexoses into and/or out of colonized cells driven by H 1 gradient generated by plasma membrane-located H 1 -ATPases, which were found to be induced upon mycorrhization (Marx et al, 1982;Gianinazzi-Pearson et al, 1991;Ferrol et al, 2002;Krajinski et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…g, Plant-derived carbon is released into the periarbuscular space probably as Suc and then cleaved into hexoses by Suc synthases (Hohnjec et al, 2003) or invertases (Schaarschmidt et al, 2006). AM fungi then acquire hexoses (Shachar-Hill et al, 1995;Solaiman and Saito, 1997) and transport them over their membrane by so far unknown hexose transporters. It is likely that these transporters are proton cotransporters as the GpMST1 described for the glomeromycotan fungus Geosiphon pyriformis (Schuessler et al, 2006).…”
Section: Ammonium and Phosphate Uptake At The Interface: A Speculativmentioning
confidence: 99%
“…There is also uncertainty as to what form of carbon is transported at these interfaces. Several approaches have indicated that glucose may be preferred over fructose or sucrose as carbohydrate imported by the fungus from the apoplastic space (Saito, 1995;Shachar-Hill et al, 1995;Solaiman and Saito, 1997;Pfeffer et al, 1999). This is then converted to lipid for transfer within the external mycelium (Pfeffer et al, 1999;Bago et al, 2002).…”
mentioning
confidence: 99%